2018
DOI: 10.1111/den.13223
|View full text |Cite
|
Sign up to set email alerts
|

Pancreatic cysts: Is the answer on the wall?

Abstract: This Editorial refers to the article by L. Baressi, p 760‐770 of this issue.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 10 publications
(15 reference statements)
0
2
0
Order By: Relevance
“…Although a close relationship between ST and pancreatic ductal carcinoma is known, the association of ST and the onset of IC have not been investigated in detail. As a method to diagnose ST directly, Nakai and Koike reported EUS‐guided through‐the‐needle biopsy such as a targeted wall puncture. Although this procedure is not common in Japan because of the risk of dissemination, they reported that it has the potential to be useful for evaluating the degree of dysplasia and stroma in BD‐ and mixed‐IPMN with ST.…”
Section: Discussionmentioning
confidence: 99%
“…Although a close relationship between ST and pancreatic ductal carcinoma is known, the association of ST and the onset of IC have not been investigated in detail. As a method to diagnose ST directly, Nakai and Koike reported EUS‐guided through‐the‐needle biopsy such as a targeted wall puncture. Although this procedure is not common in Japan because of the risk of dissemination, they reported that it has the potential to be useful for evaluating the degree of dysplasia and stroma in BD‐ and mixed‐IPMN with ST.…”
Section: Discussionmentioning
confidence: 99%
“…The transpapillary approach and EUS are useful in evaluating pancreatic cystic lesions, especially IPMN. Endoscopic diagnosis using novel techniques is useful and necessary for assessing pancreatic cystic lesions; however, clear strategies have not yet been developed . Further studies are warranted not only to improve diagnostic ability but also to determine a clear strategy for the use of novel endoscopic techniques for the diagnosis of pancreatic cystic lesions.…”
Section: Discussionmentioning
confidence: 99%